Economic burden of cervical cancer in Malaysia (Medical Journal of Indonesia, 2008)
Cervical cancers form the second highest number of female cancers in Malaysia, imposing a substantial amount of cost burden on its management. However, an estimation of cost burden of abnormal smears, cervical pre-invasive and invasive diseases needs to be done to show how much spending has been allocated to the problem. An expert panel committee came up with the clinical pathway and management algorithm ofÂ  cervical pre invasive and invasive diseases from July-December 2006 Malaysia. An activity based costing for each clinical pathway was done. Results were converted to USD. The cost of managing pre-invasive cervical cancers stage is USD 420,150 (Range: USD 197,158-879,679). Management of invasive cancer (new cases) costs USD 51,533,233.44 (Range: USD 32,405,399.69 - USD 129,014,768.40). The cost of managing existing cases is USD 17,005,966.87 (Range: USD 10,693,781.90 - USDÂ  28,901,587.12). The total cost of managing cervical cancers by health care providers in a public setting is around USD 75,888,329.45 (Range: USD 48,083,804.60 - USD 48,083,804.60). The outcome of this study has shown that preventive modalities such as screening have only contributed to 10.3 % of the total management cost of cervical cancer. The major cost contribution (67%) came from treatment of invasive cancer especially at more advanced stages of cancer, followed by treatment of existing cases (22%) and lastly on pre-invasive disease (0.6%). This study revealed that proportion of preventive modality in this country was still low, and the major cost came from actual treatment cost of cervical cancer. Therefore, heightened public cervical cancer screening in the country is needed. (Med J Indones 2008; 17: 272-80)Keywords: cervical cancers, pre invasive disease, HPV vaccination